Correlation of depression, anxiety and stress symptoms with xerostomia symptoms among medical and dentistry students in pre-clinical and clinical phase - Qushay U. Malinta; Anandha W. Yustika; Rasmidar Samad (DiscoverSys Inc., 2022)
Objective: to observe whether symptoms of depression, anxiety and stress correlates with symptoms of xerostomia among medical and dentistry students. Material and Methods: this was a cross-sectional study involving 772 medical and dentistry students in pre-clinical and clinical phase of Hasanuddin University, Makassar, Indonesia in January 2022. Chi-square test and Spearman correlation analysis were performed on the data that were obtained online via Google Form. DASS 21 questionnaire was used to identify symptoms of depression, anxiety and stress. Fox’ questionnaire was used to identify symptoms of xerostomia. Results: There were mild but significant correlations between occurrence of depression (r=0.100; p=0.006), anxiety (r=0.118; p=0.001), and stress (r=0.096; p=0.008) symptoms with symptoms of xerostomia among medical and dentistry students. Xerostomia symptoms was significantly higher (p<0.05) among dentistry students compared with medical students in both pre-clinical (64.9% vs 44.8%) and clinical (40.4% vs 27.7%) phase. In both pre-clinical and clinical phase, occurrence of depression and anxiety symptoms among medical students were not significantly different from dentistry students (p<0.05). Moderate to severe stress tend to occur more among dentistry students (p<0.05). Conclusion: Symptoms of depression, anxiety and stress correlates with symptoms of xerostomia among medical and dentistry students.